Review of Antonis Anastasopoulos (ed.), Political Initiatives 'From the Bottom Up' in the Ottoman Empire - Aksan, Virginia (Historein, 2014)
Book review of Antonis Anastasopoulos, ed. Political Initiatives "From the Bottom Up" in the Ottoman Empire. Rethymno: Crete University Press, 2012. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:13.0pt; mso-para-margin-left:0cm; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --><!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> <![endif]-->